Physical therapy in female urinary incontinence in times of COVID-19 pandemic: A contemporary proposal - Ardessore , Thais; Tropiano , Ligia Maria Canellas; Callegari , Marilia Rezende; Salerno , Gisela Rosa Franco (Seven Editora, 2023)
Introduction: Urinary incontinence is defined as a multifactorial urogynecological disorder, of high incidence, and physiotherapy is one of the main treatments indicated. Group therapies, in turn, are viable to reduce the lack of care and demonstrate good cost-effectiveness, in addition to promoting autonomy and integration among subjects, resulting in good results, when correctly indicated. Objective: to verify the effect of a group follow-up for urinary incontinence on the variables; sexual satisfaction, sleep quality, and body perception. Method: This is a case series study that followed 5 participants, mean age of 50 years, urinary losses on exertion and urgency, assessed for sleep quality (Pittsburgh Sleep Quality Index), sexual performance (Female Sexual Function Index) and body perception (Body Image Scale). The intervention consisted of 10 sessions of remote, synchronous, group physiotherapeutic telecare, based on kinesiotherapy associated with fast and slow pelvic floor fiber contractions. Results: From this intervention model, a slight worsening of sexual performance was observed, general improvement of all patients in the sleep quality variable, and significant improvement in body perception were observed. Conclusion: The FSFI Sexual Satisfaction Index showed post-intervention worsening, showing improvement only in Desire. The Pittsburgh Sleep Quality Index showed an improvement in the population's sleep quality after the intervention, but it was not enough to differentiate in the final scale. There was little suffering with the image after the physical therapy intervention using the Body Image Scale, with no significant changes with the pre-intervention result. DOI:https://doi.org/10.56238/emerrelcovid19-002